Social media marketing - Kurtzke, Simone (Henry Stewart Talks, 2015)
History of social media, Social media and the age of the customer, Social media marketing strategy, Strategy objectives: branding, Strategy objectives: reputation management, Strategy objectives: customer service, Strategy objectives: customer acquisition
Updated at 2016/10/31